Model reference adaptive control (MRAC) for temperature regulation of glycerin bleaching process / Mohd Hafiz A. Jalil @ Zainuddin - A. Jalil @ Zainuddin, Mohd Hafiz (2019)
Bleaching is a part of the crude glycerin purification process that is used for glycerin colour removal. During bleaching, proper temperature regulation throughout the heating stage is extremely important in order to shorten the heating process period and consequently minimize the batch cycle time whilst preventing product quality degradation. However, temperature regulation of the bleaching process is challenging since this process is executed in batch and may possess nonlinearities that imparted from input constraint, slow dynamic response, and exothermic characteristic. Thus, this study focus on the implementation of Model Reference Adaptive Control (MRAC) based controller for improving the temperature regulation of the glycerin bleaching process. In conjunction with this, various designs of the MRAC structure were evaluated and benchmarked with Proportional Integral Derivative (PID) based controller. In this work, two PID based controller design considered are the standard PID controller and PID with Back Calculation Anti-windup (PIDBCW). For the simulation study, the first order Autoregressive Exogenous Input (ARX) model that is developed based on the open loop step test data is used to represent the heating process of the glycerin bleaching process.